Model of Human Fetal Growth in Hypoplastic Left Heart Syndrome: Reduced Ventricular Growth Due to Decreased Ventricular Filling and Altered Shape - Dewan, Sukriti; Krishnamurthy, Adarsh; Kole, Devleena; Conca, Giulia; Kerckhoffs, Roy; Puchalski, Michael D.; Omens, Jeffrey H.; Sun, Heather; Nigam, Vishal; McCulloch, Andrew D. (Frontiers in Pediatrics, 2017)
Introduction: Hypoplastic left heart syndrome (HLHS) is a congenital condition with an under-developed left ventricle (LV) that provides inadequate systemic blood flow postnatally. The development of HLHS is postulated to be due to altered biomechanical stimuli during gestation. Predicting LV size at birth using mid-gestation fetal echocardiography is a clinical challenge critical to prognostic counseling. Hypothesis: We hypothesized that decreased ventricular filling in utero due to mitral stenosis may reduce LV growth in the fetal heart via mechanical growth signaling. Methods: We developed a novel finite element (FE) model of the human fetal heart in which cardiac myocyte growth rates are a function of fiber and cross-fiber strains, which is affected by altered ventricular filling, to simulate alterations in LV growth and remodeling. Model results were tested with echocardiogram measurements from normal and HLHS fetal hearts. Results: A strain-based fetal growth model with a normal 22 week ventricular filling (1.04 ml) was able to replicate published measurements of changes between mid-gestation to birth of mean LV end diastolic volume (EDV) (1.1 to 8.3 ml) and dimensions (long-axis 18 to 35mm; short-axis 9 to 18mm) within 15% RMSD error. By decreasing volumetric load (-25%) at mid-gestation in the model, which emulates mitral stenosis in utero, a 65% reduction in LV EDV and a 46% reduction in LV wall volume were predicted at birth, similar to observations in HLHS patients. In retrospective blinded case studies for HLHS, using mid-gestation echocardiographic data, the model predicted a borderline and severe hypoplastic LV, consistent with the patients’ late-gestation data in both cases. Notably the model prediction was validated by testing for changes in LV shape in the model against clinical data for each HLHS case study. Conclusion: Reduced ventricular filling and altered shape may lead to reduced LV growth and a hypoplastic phenotype by reducing myocardial strains that serve as a myocyte growth stimulus. The human fetal growth model presented here may lead to a clinical tool that can help predict LV size and shape at birth based on mid-gestation LV echocardiographic measurements.